Pengaruh Gaya Kepemimpinan, Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Guru di UPTD SDN 15 Pinang Damai - Fadilla Lesmana; Novrihan Leily Nasution; Aulia Indra (Departement of Mathematics Education, 2023)
This study aims to analyze the effect of leadership, work environment, and work discipline on teacher performance, partially and simultaneously. Teacher performance plays an important role for the advancement of education in Indonesia, especially in UPTD SDN 15 Pinang Damai, less than optimal teacher performance which results in program targets not being optimal. Given the importance of teacher performance in order to achieve educational goals optimally, encouraging researchers to conduct research with the title